Comparative Analysis of Serum Trace Elements and Nephrotoxic Elements between Diabetic Nephropathy and Non-Diabetic Kidney Disease Patients - Shabbi, Fatimah Ali; Ali, Sayed Ibrahim; Abdulqader, Ahmad Al; Al Khashram, Nawaf; Shabbi, Layla Ali; Dinesh, Deepthy Kunnathully; Malik, Maujid Masood; Hamdan, Hamdan Z.; Mohamedain, Ahmed (South Eastern European Journal of Public Health, 2025)
Background: Diabetic nephropathy (DN) is a major complication of diabetes mellitus and a significant contributor to end-stage renal disease (ESRD). This study investigates the relationship between serum trace elements (Zn, Cu, Mg, Fe) and nephrotoxic elements (As, Pb, Cd, Hg) with renal function in diabetic patients with nephropathy, diabetic patients without nephropathy and non-diabetic chronic kidney disease patients, in addition to controls. Methods: A cross-sectional study was conducted at King Abdulaziz Air Base Hospital, Dhahran, from December 2021 to May 2022, involving 123 participants divided into four groups: diabetic nephropathy, diabetes without nephropathy, chronic kidney disease (CKD), and healthy controls. Serum levels of trace and nephrotoxic elements were measured using inductively coupled plasma mass spectrometry. Renal function tests and glycated hemoglobin (HbA1c) levels were also measured. Pearson's and Spearman's correlation analyses were performed to assess the relationships between these element levels and renal function. Results: The mean (SD) serum levels of Zn 85 (25) μg/dL and Cu 110 (35) μg/dL were significantly higher in the diabetic nephropathy group, while Fe 17.3 (6.9) μmol/L, As 0.33 (0.74) μg/dL, and Pb 7.7 (2.3) μg/dL were significantly higher in the diabetes without nephropathy group. Only serum magnesium levels were significantly higher in the chronic kidney disease group. Interestingly, mercury was highest in the control group at 1.14 (0.81) μg/dL. Serum creatinine showed direct correlations with trace elements Zn (r = 0.406) and Cu (r = 0.358), and with nephrotoxic elements As (r = 0.328), Pb (r = 0.384), and Hg (r = 0.287). HbA1c was positively correlated with Zn (r = 0.307), As (r = 0.309), and Pb (r = 0.365), while it was inversely correlated with Mg (r = -0.308) and Fe (r = -0.359). Conclusion: In this study, trace elements Zn and Cu, as well as toxic elements As and Pb, were positively correlated with serum creatinine and negatively impacted renal function. Glycated hemoglobin was positively correlated with Zn, As, and Pb, while it was inversely correlated with Mg and Fe. Both trace and toxic elements are associated with renal function and HbA1c, highlighting the need for further research.